Hijab envy': the visible angst of immigrant Christians in a pluralist Canada - Macdonald, Arlene (Journal of contemporary religion, 2018)
This article explores the predilection of Christians of immigrant background to perceive themselves as a disadvantaged group in the new reality of Canada's growing religious diversity. The present inquiry challenges loss as the definitive emotional register for Christian engagement with Canada's new religious minorities, demonstrating that religious minorities have elicited begrudging admiration and envy from their Christian counterparts. This inquiry insists that contemporary Canada, not Christian Canada', is the most important frame for understanding the perceptions and predilections of the Christians in this study. It argues that pluralist ideals, the policy instruments, and social practices that carry these ideals and the cultural forums that display and debate these ideals shape not only the attitudes' of young Christians, but also the regimes of visibility in which and from which they operate. While scholars impute an increasing visibility to religion, this article demonstrates that the array of affects between viewer and viewed are highly variable and context specific.